APLICAÇÃO DO EXTRATO DE PRÓPOLIS VERMELHA COMO ANTIOXIDANTE NATURAL EM HAMBÚRGUERES DE FRANGO - ALVES, Renata de Araújo (2023)
Burgers are highly popular foods. However, they are susceptible to lipid oxidation and other deteriorating activities during production and storage. Therefore, the aim of this study was to evaluate the red propolis hydroalcoholic extract (RPE) use in the conservation of chicken burgers during frozen storage for 120 days, as well as to evaluate the sensory acceptance of this product. For this, 4 treatments were elaborated, being T1 – without antioxidant addition, T2 – with 0.1g/kg of commercial antioxidant, T3 – with 0.3g/kg of RPE and T3 – with 0. 6g/kg of RPE. Treatments were evaluated for pH, total volatile bases, color and lipid oxidation on days 0, 30, 60, 90 and 120 of storage. Moreover, a consumer survey was carried out, through the focus group and consumer attitude, and sensory evaluation applying the hedonic scale, just- about-right scale, CATA and purchase intention. The red propolis extract showed an efficient result for lipid oxidation and for the color parameters redness a* and yellowness*. However, it was not efficient for the preservation of pH and total volatile bases. Data for the focus group showed that consumers relate chicken burgers with RPE to a healthy food, which was also reinforced in the word association methodology, where image of burger was associated with sensory characteristics, health and diet. All sensory attributes received grades between “I liked it moderately” and “I liked it a lot” on the hedonic scale, demonstrating good acceptance by consumers, who also judged the “bitter taste” of the burgers as “just-about-right”, while for the term “chicken flavor” only for the treatment containing lower RPE concentration (0.3RPE) was considered just-about-right. For the purchase intention, all treatments obtained percentages above 70% in the will buy region, with emphasis on the treatment containing the highest concentration of RPE (0.6RPE). Thus, the red propolis use was positive in terms of lipid oxidation, color parameters and also obtained good acceptance by consumers.